31-YEAR DYNAMICS OF THE SCREENING LEVEL OF AWARENESS OF THE ABORIGINAL AND IMMIGRANT POPULATION REGARDING HYPERTENSIVE CONDITIONS AND PHARMACOLOGICAL PRESCRIPTION - Mamasaliev N. S.; Qalandarov D. M.; Salohiddinov A. S.; Usmonov B. U.; Mamasolieva Sh. A. (Modern American Journals, 2025)
The analysis of the literature data on the use of modern organizational technologies for the prevention of hypertension is carried out. The basic principles and stages of diagnosis of this pathology, risk groups for the development of arterial hypertension, and features of the organization of preventive programs are considered. The basic principles of the application of the blood pressure selfmonitoring system in organizations and public places are considered.
Keywords: Arterial hypertension, prevention of cardiovascular diseases, organizational technologies, self-monitoring of blood pressure, patient education, hypertension, prevention, scientific basis, screening, territory